Leasing pracowniczy jako jedna z metod łagodzenia napięć wywołanych sezonowością zatrudnienia - Wrzosek, Krystyna (Employee leasing as a method of reducing tensions caused by seasonal employment, 2005)
Employee leasing is a relatively new form of acquiring and employing workers in Poland. It lets companies flexibly adapt their employment to changing needs. Because of its advantages employee leasing can be used to provide required seasonal labour, but this use is limited both by nature of employee leasing and by law regulating an employment of seasonal workers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 635-645